METODE ROLE PLAYING BERORIENTASI KEARIFAN LOKAL SEBAGAI SARANA BAGI SISWA DALAM MEMAHAMI NILAI-NILAI PANCASILA DAN KARAKTER PADA KURIKULUM MERDEKA: SYSTEMATIC LITERATURE REVIEW - Arianti, Rosmalinda Eka; Puspita, Ari Metalin Ika; Setyowati, Raden Roro Nanik (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to present empirical data on the results of previous research so that teachers have a reference as a basis to further explore the Role Playing Method oriented to local wisdom as a means for students to understand the values of Pancasila and the character in the Independent Curriculum. The method used is qualitative descriptive with a Systematic Literature Review (SLR) design. Based on the results and discussions, one hundred and two items were obtained with eighteen clusters. The results of VOS viewer's visualization by making the Role Playing Method the main focus also show that there is no connection with local wisdom keywords, which means that there are limitations in connection or integration. In fact, in the context of Pancasila values and character, the role of teachers as facilitators allows students to learn through simulations of real situations, so that the understanding of these values can be better internalized. However, these ideal conditions do not show a connection. Thus, it can be concluded that the application of the Role Playing Method is still isolated and less oriented to aspects of local wisdom in the context of understanding Pancasila values and character. The lack of this connection shows that there is an opportunity for further research to explore the relationship between the application of the Role Playing Method, local wisdom, and Pancasila values and character.